The Risks of Femoral Nailing in the Positioning of Hemilithotomy on Traction Table Getting A Contralateral Well-Legdrop-Foot (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Postoperative contra lateral morbidity following fracture fixation surgery is rare due tohemilithotomy placement on traction table. Following a typical orthopedic femoral nailing, we should notea case of unexplained typical peroneal nerve palsy formed on the contra lateral side, manifesting with dropfoot.Case report: After prolonged femoral nailing, a 32-year-old male suffered an uncommon common peronealnerve palsy that manifested itself toward lateral drop foot. This iatrogenic and intermittent disorder wasdelineated to be position-related neuropraxia after neurophysiological analysis and review of applicableliterature.Conclusion: Place modification at intervals or complete avoidance of excessive hyperflexion of the knee isadvised to prevent typical peroneal nerve morbidity against the lateral.
Keywords: foot drop, fracture of shaft of femur, common peroneal nerve palsy